Liquid metal injected from interstitial channels for inhibiting subcutaneous hepatoma growth and improving MRI/MAT image contrast - Lu, Chaosen; Yang, Aocai; Xia, Fei; Liu, Guoqiang; Zhao, Hongliang; Zhang, Wenwei; Li, Yuanyuan; Liu, Jian; Ma, Guolin; Xia, Hui (Frontiers in Oncology, 2022)
Currently, a series of research on liquid metal (LM) have been studied as biomedical materials for medical therapy.But the most application of LM in medical therapy are taking LM as a carrier for oncology therapeutics and the feasibility and effect of LM in directly tumor treatment are not considered and verified, and how to find the negative resection margin of tumor is also a fatal problem in surgery. We aimed to inject LM into interstitial channels of extremities of mice to overlay the surface of primary tumor to research the inhibition of LM for tumor growth and indicate the the negative resection margin of tumor. In this study, we injected LM into the forelimb interstitial channel of the BALB/c-nu female mice with hepatoma. The negative resection margin of tumor displayed by LM and the distribution of LM in body were observed by MRI T2 and MAT, both the results of tumor volume change ratio in each group and blood test were analyzsed by statistics, and the biological safety and compatibility of LM were evaluated by Histopathological analysis blood tests. The results of experiments in this paper shown that LM injected in forelimb interstitial channel can be delivered to the surface of hepatomal tumor and inhibited the growth of primary tumor by causing closing effect toward tumor. The statistical results that the volume and volume change ratio of tumor of female BALB/c-nude mice in LM group are lower than mice in other groups evidenced that the inhibition of LM for the proliferation of hepatocellular carcinoma in animal, and the distribution of LM in vivo could be clearly observed under T2WI anatomic images and cross-profile of tumor in MAT. LM also has obvious contrast in MRI T2 scanning and enhanced the amplitude of imaging signal in MAT, it manifests that LM has the potential to be a contrast in MRI and be a novel favorable dielectrics for MAT. All in all, the finds above mentioned indicate that LM not only could inhibit the growth of hepatocellular carcinoma in vivo, is feasible to be a tissue contrast on MRI and MAT.